2022
DOI: 10.1177/19476035221118165
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Small Noncoding RNA Expression during Chondrocyte Senescence

Abstract: Objective Osteoarthritis (OA) is characterized by the chronic and progressive deterioration of articular cartilage. Chondrocyte senescence could lead to a shift in the balance between extracellular matrix (ECM) component synthesis and degradation. Small noncoding RNAs (sncRNAs), including microRNAs (miRNAs), P-element-induced wimpy testis-(PIWI-) interacting RNAs (piRNAs), small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs), and repeat-associated siRNAs (rasiRNAs), are a class of important epigenetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Xiao F et al found 40 microRNAs upregulated and 70 downregulated in senescent chondrocytes, of which inhibition of miR-132-5p prevented chondrocyte senescence [139]. Furthermore, 8 piRNAs were upregulated while 17 were downregulated, with a dominant species piR_025576 delaying chondrocyte senescence.…”
Section: Regulation Of Senescence At the Post-transcriptional Level W...mentioning
confidence: 99%
“…Xiao F et al found 40 microRNAs upregulated and 70 downregulated in senescent chondrocytes, of which inhibition of miR-132-5p prevented chondrocyte senescence [139]. Furthermore, 8 piRNAs were upregulated while 17 were downregulated, with a dominant species piR_025576 delaying chondrocyte senescence.…”
Section: Regulation Of Senescence At the Post-transcriptional Level W...mentioning
confidence: 99%
“…Inhibition of miR-181a-5p using antisense oligonucleotides alleviated the severity of cartilage degeneration of facet joints [ 26 ]. Non-coding RNAs including microRNAs play an important role in chondrocyte senescence [ 27 ]. MiR-29b-5p has been reported to alleviate chondrocyte senescence with reduced p21 and p16 expression [ 28 ].…”
Section: Introductionmentioning
confidence: 99%